Numerical analysis of single SC-50-800 and SC-50-500x2-x4 group centrifugal cyclones: efficiency comparison - Madaliev, Murodil; Usmonov, Mavlonbek; Kadyrov, Khasanboy; Abdullajonov, Nurzoda; Mavlonova, Dilnoza; Otakhanova, Zamira; Muminov, Kamolkhan (E3S web of conferences, 2024)
Centrifugal cyclones are important devices used to separate solids or liquids from gas streams using centrifugal forces. They are widely used in various industrial processes and air and gas purification systems. In this work, numerical modeling and study of the efficiency of cyclones of various configurations are carried out: single cyclone SC-50-800, group cyclones SC-50-500x2 and SC-50-400x4. To conduct the study, the engineering software package Comsol Multiphysics 6.1 was used with the addition of the Flow Simulation module, specialized for modeling hydrodynamic processes. To simulate turbulent flows, the v2-f model was chosen, which is often used in the case of swirling flows. The computational experiment was carried out at a constant air flow rate of 4500 m3/h. Based on the obtained numerical data, an analysis of the effectiveness of various cyclone configurations was carried out. The results of the study show that the operating efficiency of group cyclones significantly exceeds the efficiency of single cyclones. This is confirmed by analysis of separation parameters and comparison of performance indicators of various cyclone configurations. The data obtained can be useful for the design and optimization of gas stream purification systems in various industrial and environmental applications.